Comparative efficacy of tofacitinib and adalimumab in patients with psoriatic arthritis in real clinical practice. Data from the Russian nationwide register of patients with psoriatic arthritis - E. Yu. Loginova; T. V. Korotaeva; E. E. Gubar; Yu. L. Korsakova; S. I. Glukhova; E. A. Vasilenko; A. A. Vasilenko; N. A. Kuznetsova; I. M. Patrikeyeva; E. L. Nasonov (Современная ревматология, 2021)
Objective: to compare the clinical efficacy in real clinical practice of the targeted synthetic disease-modifying antirheumatic drug (sDMARD) tofacitinib (TOFA) and the biologic DMARD (bDMARD), an inhibitor of tumor necrosis factor alpha (TNFα), adalimumab (ADA) in patients with psoriatic arthritis (PsA), included in the Russian nationwide register of patients with PsA.Patients and methods. The study included 77 patients with PsA (43 men and 34 women) who met the CASPAR criteria and were observed in the Russian nationwide register. Patients were divided into two groups depending on the treatment. Group 1, in which oral TOFA was prescribed, 5 mg 2 times a day, included 41 patients: 24 (58.5%) men and 17 (41.5%) women, the median age was 41 [34; 50] years, the median duration of PsA was 72 [35; 120] months. Group 2, in which subcutaneous ADA was used, 40 mg every 2 weeks, included 36 patients: 19 (52.8%) men and 17 (47.2%) women, the median age was 44 [34; 51] years, the median duration of PsA was 59 [22; 102] months. Combination therapy, including methotrexate (MT), received 80.5% of patients in the TOFA group and 52.8% of patients in the ADA group. At the beginning of the study and every 6 months further, the activity and efficacy of PsA therapy were assessed in all patients according to DAPSA and criteria for minimal disease activity – MDA (number of painful joints ≤1, number of swollen joints ≤1, PASI ≤1 or BSA ≤3 , pain score ≤15, patient's general assessment of disease activity ≤20 mm on a visual analogue scale, HAQ ≤0.5, enthesitis ≤1), dynamics of BASDAI and BSA were also assessed. The number of patients who achieved remission (DAPSA ≤4) or MDA (5 criteria out of 7) during therapy with TOFA and ADA was determined.Results and discussion. Before the start of the therapy in the 1st group, the median DAPSA was 44.2 [37.8; 55.3]: moderate PsA activity was in 5 (12.2%) patients, high in 36 (87.8%) patients. In group 2, the median DAPSA was 35.8 [21.1; 52]: low activity was detected in 3 (8.6%), moderate – in 11 (31.4%), high – in 21 (60%) patients (data from 35 patients was available). 6 months after the start of treatment in patients of the 1st and the 2nd group, there was a significant decrease in all indicators of PsA activity compared to the baseline. The median DAPSA was 11 [4.3; 17.3] and 9.1 [6; 19.6]; remissions according to DAPSA reached 11 (26.8%) and 6 (20.8%) patients, respectively, low activity – 15 (36.6%) and 13 (44.8%), MDA – 16 (40%) and 9 (30%). The number of patients with dactylitis in the 1st and in the 2nd group significantly decreased: from 22 (53.7%) to 5 (13.2%) and from 13 (36.1%) to 6 (20%), respectively. Median HAQ decreased from 1 [0.625; 1.5] to 0.5 [0; 0.875] and from 0.875 [0.5; 1.38] to 0.5 [0; 0.875]; median BASDAI – from 6 [4.2; 7] to 1.4 [0.6; 3.2] and from 4.4 [1.9; 5.8] to 3 [0.8; 4.5], respectively. In group 1, the number of patients with BSA> 3% decreased from 16 (39%) to 8 (26.7%; p<0.225), and in group 2, due to insufficient data (5 patients), we failed to evaluate BSA dynamics.Conclusion. In real clinical practice TOFA and ADA both had comparable efficacy on all clinical manifestations of PsA: after 6 months of therapy, most patients with PsA achieved MDA, low disease activity and remission according to DAPSA and BASDAI.